Inequalities in public water supply fluoridation in Brazil: An ecological study - Moysés Simone T; Olandoski Marcia; da Silva Wander J; Gabardo Marilisa CL; Moysés Samuel J (BMC, 2008)
Abstract Background The literature is scarce on the social and geographic inequalities in the access to and implementation of the fluoridation of public water supplies. This study adds knowledge to the Brazilian experience of the chronic privation of water and wastewater policies, access to potable water and fluoridation in the country. Thus, the aim of this study was to verify possible inequalities in the population's access to fluoridated drinking water in 246 Brazilian municipalities. Methods The information on the process of water fluoridation in the municipalities and in the macro region in which each municipality is located was obtained from the national epidemiological survey which was concluded in 2003. The data relating to the human development index at municipal level (HDI-M) and access to mains water came from the Brazilian Human Development Atlas, whilst the size of the population was obtained from a governmental source. The Fisher exact test (P < 0.05) was employed to identify significant associations between the explanatory variables and their ability to predict the principal outcomes of interest to this study, namely the presence or absence of the water fluoridation process in the municipalities as well as the length of time during which this measure has been implemented. Linear regression was used to observe the associations between the relevant variables in a multivariate environment. Results The results clearly showed that there is a relationship between municipalities with larger populations, located in more socio-economically advantaged regions and with better HDI-M, and where fluoridation is both present and has been implemented for a longer period of time (started before 1990). Conclusion The findings suggest that the aim of treating water with fluoride may not be being adequately achieved, requiring more effective strategies so that access to this measure can be expanded equitably.